TINJAUAN YURIDIS TERHADAP PELAKSANAAN KETERBUKAAN INFORMASI PUBLIK BERDASARKAN UNDANG-UNDANG NOMOR 14 TAHUN 2008 TENTANG KETERBUKAAN INFORMASI PUBLIK - Wisanggeni, Dimas; Sidarta, Dudik Djaja; Ayuningtyas, Fitri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Law No. 14 of 2008 on Public Information Disclosure (KIP Law) is a vital legal instrument for guaranteeing the public’s right to information in order to realise transparent governance. This study examines the legal implementation of the KIP Law, focusing on analysing the implementation of public agencies’ obligations and identifying factors that hinder its effectiveness. The purpose of this study is to evaluate the extent to which the principle of information disclosure has been implemented and to identify legal obstacles in its implementation. This study is an empirical legal study using a qualitative approach. Data was obtained through a study of legislation, legal literature, and interviews with relevant parties at [Name of Public Agency/Research Location]. Data analysis was conducted using descriptive-analytical methods. The results of the study found that the implementation of PUBLIC INFORMATION DISCLOSURE LAW NUMBER 14 OF 2008 has not been fully effective. The main obstacles encountered include: (1) the suboptimal function and role of the Information and Documentation Management Officer (PPID); (2) a strong bureaucratic culture that is resistant to change; and (3) a lack of understanding and commitment from public agency officials in providing information. As a result, the fulfilment of the public’s right to information is often hampered. To overcome this, efforts are needed to strengthen the PPID institution, increase human resource capacity, and enforce stricter sanctions for public agencies that do not comply with the provisions of the KIP Law